The Development of “Poster Equipped with Video (POSEVI)” on Fluids at Rest Topic for 11th Grade Students - Karunia Puji Lestari; Hadi Nasbey; Raihanati Raihanati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This study aims to develop products such as “Poster equipped with Video (POSEVI)” that worth to used as a physics learning media for high school students with fluids at rest material. POSEVI is an educational poster equipped with educational videos, so the students shall receive visual learning (through poster) and audio-visual learning (through video). The videos contained by POSEVI can be accessed by scanning QR Codes printed on the poster. POSEVI was designed by using the research & development method that looked up to the ADDIE development model. At the beginning of this research, the need assessment questionnaire had shared as early research. In the Design stage, we should have inserted the material and contents into the poster and video. Then, in the Develop stage, POSEVI was validated by expert validators to learn how feasible the product is according to the result from expert validators. By the implementation stage, the field test was conducted limitedly by involving the XI grade students to learn about POSEVI’s feasibility as a learning media after revising and correcting from the expert validator. The final of this research is an evaluation by revising that one may accomplish POSEVI as physics’ learning media compatible with students.